Relationship of Age and Different Histological Types of Ovarian Tumors (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Ovarian tumours are common problem in gynaecology and have varied age of appearance of different histopathological types.Objective: This study was undertaken to find out the relationship of age and different histological types of ovarian tumors Methods: A retrospective study was carried out in the Department of Obstetrics and Gynaecology and Department of Pathology, Sir Salimullah Medical College and Mitford Hospital, Dhaka, during May 2010 and December 2014. Five hundred forty seven (547) cases of ovarian tumours were studied in respect to their age and histopathological appearance.Results: The range of age of patients with ovarian tumour was 11 – 82 years. About 63% malignant and 73% benign ovarian tumours were found in the age group of 20 – 49 yrs. About 31% malignant ovarian tumours and 15% Benign tumours occurred in menopausal woman (≤50 yrs.). Overall, mean age of presentation of ovarian tumours was 34.29± 12.84 yrs. Mean age of patients with malignant ovarian tumour was 40.29± 14.28 (median 40 yrs; mode 45 yrs.). Mean age of benign ovarian tumour was 34.69 ± 13.08 (median 34 yrs; mode 40yrs) and mean age for borderline tumours 32.75 ± 11.70 mm (median 33 yrs., mode 20 yrs.). Mean age of non tumour ovarian masses / cysts was 31.14± 10.76 yrs (median 29.5; mode 25.4). The difference of mean age of occurance of malignant and benign ovarian tumours were statistically significant P. Dysgerminoma (mean age 23.5± 4.43) and yolk sac tumour (mean age 18 .00 ± 5.00 yrs) occurred in younger patients. Serous cyst adenocarcinoma, endometriod carcinoma and poorly differentiated carcinoma occurred around 45 years of age. Mean age of presentation of most of the benign ovarian tumours was between 30 – 37 yrs.; except thecoma which occurred in extremes of age.Conclusion: Most of the patients with malignant and benign ovarian tumours have presented in reproductive age adult women (20 – 49 yrs.); and some specific varieties of tumour (e.g. thecoma) presented in the extremes of age.Bangladesh J Obstet Gynaecol, 2017; Vol. 32(2) : 99-105